CLINICAL CASE OF USAGE OF SERELAXIN IN THE PATIENT WITH ACUTE DECOMPENSATED HEART FAILURE - I. V. Zhirov; S. N. Nasonova; S. N. Tereshchenko; O. A. Nikolaeva; T. M. Uskach (Российский кардиологический журнал)
Heart failure remains one of the main problems in contemporary cardiology, taken high frequency of hospitalizations due to acute decompensation, and worse prognosis for this category of patients. One of the drugs influencing prognosis is serelaxin (recombinant human relaxin-2). Experience of serelaxin usage as 48-hour infusion for patients with ADHF showed rapid positive influence of the drug on clinical signs and symptoms, target organ damage markers (BNP, creatinine), hemodynamics parameters (MPAP).